Para uma sócio-história da língua Guarani no Espírito Santo : uma análise sob a perspectiva sociolinguística - Calazans, Poliana Claudiano (2014)
It is estimated that there are about 50 thousand Indians from the Guarani tribe in Brazil and they are situated mainly in the coastal area of the southern states until the capixaba territory in Espírito Santo. Considering that this community keeps itself bilingual, the present work has the objective to discuss the sociolinguistic factors that led up to the maintenance of the Guarani language in the spoken Portuguese. In order to reach that objective, a corpus was created based on interviews made in the villages ranging from historic traditions, family, religion, economy and the environment (these aspects were considered by them as the main weapons against the resistance of this people). The analysis was based on the assumptions of sociolinguistics and linguistic contact, by theorists like Weinreich (1953), Fishman (1968; 1972), Appel e Muysken (1996), Coulmas (2005) among others, who discussed pertinent subjects related to the research: the linguistic contact and the maintenance/substitution of minority languages. It was also believed, that besides the contact with the Portuguese language by the commercialization of handicrafts, by the media and by the co-operation of schools aiming to integrate them, laid down by the Indian Statute, the Guarani people maintains its mother-tongue, even if it's stigmatized due to the strong religious beliefs that guide their way of living. They understand the word as a gift and give a mythic power to it, a power that connects the spiritual world, which gives extreme importance to this minority language and favors its preservation as an important imprint of their culture and their identity.